High-intensity interval exercise enhances vascular function to a greater extent than moderate-intensity continuous aerobic exercise: A case study report - Paravlić, Armin; Iskra, Simon; Turnšek, Gašper; Drole, Kristina (Annales Kinesiologiae, 2025)
This case study compared the acute effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on vascular and microvascular function in a healthy male subject (age: 34 yrs; body mass index: 25.82 kg/m2). Key vascular parameters were assessed, including augmentation index (AIx), carotid-femoral and brachial-ankle pulse wave velocity (cfPWV, baPWV), flow-mediated slowing (FMS%), and tissue saturation index (TSI) recovery slope. HIIT induced a greater reduction in baPWV (mean difference [MD]: 0.9 m/s) and a higher increase in FMS% (MD: 8%) compared to MICT, indicating more favourable changes in peripheral arterial stiffness and endothelial function. Additionally, the reoxygenation slope for TSI was more pronounced after HIIT, suggesting improved microvascular recovery. Interestingly, AIx increased following MICT (MD from baseline: 11%) but slightly decreased after HIIT (MD from baseline: −5%). These findings suggest that exercise intensity plays a critical role in determining vascular adaptations, with HIIT showing superior acute benefits.